Integral use of cupuassu in baking (Research, Society and Development, 2022)
Cupuassu amazon fruit has been show exotic flavor and rich nutritional properties. However, pulp subproduct has large volume of agro-industrial residues. This work aims full use of cupuassu in the elaboration of a bakery product. Pulp pH analyzes were performed; analysis of moisture, ash, protein, lipid and total carbohydrate composition of cupuassu pulp, peel and seeds; sensory analysis of the product was developed. The pulp had a pH of 3.65 and the highest moisture contents were obtained there. The seeds, on the other hand, had higher ash and lipid contents. While the peels showed higher values of total carbohydrates. The panettone with cupuaçu peel flour, stuffed with cupuaçu and cupulate jelly was well accepted among the evaluators, obtaining a maximum score on the hedonic scale with 73% for flavor and above 50% for aroma, appearance and texture items. As for the consumption intention, 58.1% of the tasters would always eat it and more than 80% would certainly buy the product. Cupuassu panettone and its agro-industrial residues presented a product with greater nutritional value, presence of bioactive compounds and sensorially accepted by potential consumers, indicating that it is an option for rational and sustainable use of raw material, reducing costs and waste, valuing the fruit and the cupuassu production chain economic in the Amazon region.